Peer Group Dynamics and its Influence on Adolescent Risk Behavior - Warin, Araya Kanchanapisek (Bulletin of Science, Technology and Society, 2023)
This study aims to examine the influence of peer pressure on risky behavior decision making in adolescents, as well as factors that can strengthen or reduce this influence. Peer pressure is often the main factor in adolescents' decisions to engage in risky behavior, such as smoking, consuming alcohol, and unsafe sexual behavior. This study uses a literature review approach by analyzing various related references, both social and psychological theories and relevant previous research. The results of the study show that the need for adolescents to be accepted into their social groups and the influence of social anxiety can reinforce peer pressure. However, individual factors such as self-esteem, self-control, and positive family and environmental support can reduce the negative impact of group pressure. In addition, involvement in extracurricular activities and strong relationships with parents have also been shown to be important in reducing the tendency for adolescents to engage in risky behavior. This study concludes that although peer pressure can greatly influence adolescent behavior, reinforcing factors in their lives can help reduce this impact. Therefore, it is important for parents, educators, and the community to create an environment that supports the positive development of adolescents.